Jasper-Stone Like Skull: Massive Skull Metastasis With Invasion of Leptomeninges-A Rare Case Report - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2013)
Skull metastases are common; lung cancer composes 14% of them. Destructive, whole calvarial infiltration of lung cancer has not been reported before. A 63-year-old male patient was admitted to our clinic with multiple palpable masses all over his head. Plain skull radiography depicted diffuse bony thickening. On MRI, whole calvarium enhanced on T1-weighted scans. PET-CT showed increased uptake in lung which was proved to be non-small cell lung cancer after bronchoscopic biopsy. En bloc resection for the biggest calvarial lesion was done with success. Pathology was consistent with metastasis. Destructive skull metastasis with full bone involvement can be the first presenting sign of primary lung cancer as presented in this case report.
Keywords: Lung cancer; metastasis; PET-CT; biopsy